Seleksi dan Identifikasi Bakteri Antagonis sebagai Agens Pengendali Hayati Penyakit Hawar Pelepah Padi - Rustam, Rustam; Giyanto, Giyanto; Wiyono, Suryo; Santosa, Dwi Andreas; Susanto, Slamet (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Selection and identification of effective microbes are important steps to obtain biological control agents. The objective of this research was to screen potential bacteria as controlling agents for rice sheath blight disease. The research was conducted at plant bacteriological laboratory and green house of Plant Protection Division of Bogor Agricultural University, Bogor, from May 2010 to February 2011. The trial was arranged in a completely randomized design with bacterial isolates as treatment. The result showed that 30 out of 144 bacterial isolates indicated an antifungal activity to R. solani. In vivo test indicated that 3 of the 30 isolates which have antifungal activity were able significantly to suppress the rice sheath blight disease. Those isolates were marked as TT47, SS19 and BR2, with the ability to suppress rice sheath blight disease at rate of 79.6, 56.4, and 49.4%, disease index 1.7, 3.7, and 4.3, and the disease incidence 33.3%, 73.35, and 80%, respectively. Molecular characterization of partial sequence of 16S rRNA on SS19, TT47, and BR2 isolates showed that those bacteria are Serratia marcescens, Ralstonia pickettii, and Bacillus subtilis, respectively.